Reflection on the original peoples of the pacific, central and northern Nicaragua (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
Throughout Nicaragua, we find different cultural expressions of indigenous peoples, who struggle hard to conserve their forests, their traditions, forms of social organization, ways of doing politics and maneuvering their economic and social affairs in full freedom. Despite this, the indigenous peoples of north central Nicaragua find themselves in a complex ethnic labyrinth, assuming false positives in relation to their historical origin. That is, the construction of discourse and ethnic identity in some towns in the center and north, revolves around a false cultural positive called «Chorotega», this assertion distorts much of the history of the indigenous peoples of the Segovia. In the present essay, I will approach the ethnic and political plots related to the cultural identity of the indigenous peoples of the north center of Nicaragua, who assume a cultural identity that does not agree with the history, linguistics and anthropology of the region. Said essay, has the purpose of vindicating beyond, of the practices and traditions the subjects of the ethnic selfidentification, in the original communities of the Segovia. To do this, I returned to elements of cultural anthropology and national archeology, to elucidate the origins and historical processes of the peoples in question.Likewise, the hypothesis that I place in the national anthropology has as its base, to debate the discourse of the people denominated «Chorotega of the center and north» through the primary registers, the results of the archeology in the last 20 years, in the central region and north. Also, we will resume the linguistic studies of Alfonso Cónstenla in the aforementioned region. Starting from an interdisciplinary current of southern anthropology, which promotes the recognition of the original identity of peoples, from their ethnic origin, common history, daily practices and postmodern socio-cultural structure in the region.
Keywords: cultural origin; ethnic identity; self identification; peoples of the Segovia; false positives